Increased expression profile of NCSTN, Notch and PI3K/AKT3 in hidradenitis suppurativa. (5th November 2020) - Hessam, S.; Gambichler, T.; Skrygan, M.; Scholl, L.; Sand, M.; Meyer, T.; Stockfleth, E.; Bechara, F.G.
Abstract: Background: In a small number of kindreds with familial hidradenitis suppurativa (HS) different mutations of NCSTN (nicastrin) have been identified. Blocking of NCSTN leads to impairment of the Notch and PI3K/AKT signalling pathway, which is assumed to play a pathogenic role in HS. However, very limited data are available concerning expression levels of these pathway components in HS skin. Objectives: To analyse the mRNA and protein expression of NCSTN, Notch1–3, PIK3R3 and AKT3 in HS. Methods: Skin samples from healthy controls, lesional and perilesional skin of HS patients with and without a positive family history were analysed by quantitative real‐time RT‐PCR and immunohistochemistry. Univariate statistical analyses were conducted regarding association between expression levels and patient's characteristics. Results: Expression levels of all investigated genes showed significantly higher levels in lesional HS skin compared with healthy controls. Univariate analysis showed no association between a positive family history and mRNA expression levels. Perilesional HS skin of patients with mild disease severity (Hurley I) showed significant higher mRNA expression levels of the investigated pathway components compared to moderate (Hurley II) and severe disease (Hurley III). Conclusion: We found no evidence for diminished expression levels of the Notch signalling. In contrast, the NCSTN, Notch and PI3K/AKT signalling components are overexpressed in HS. Future research is needed to investigate a possible pathogenetic role or to reveal a coactivation of these overexpressed components during inflammatory response in HS.